Propuesta para el manejo y disposición de los residuos sólidos generados en el municipio de Muzo, Boyacá (2016)
The intention of this project is to generate an offer that involves the integral management of solid waste generated in the municipality of Muzo, Boyaca. To know the quantities generated of every residue, a characterization was carried out for a week. Then, different alternatives were proposed and the most suitable alternative was selected by the fuzzy tops is method. For the treatment for the solid organic residues there was proposed an anaerobic static composting with forced aeration in order to evaluated four carbon-nitrogen initial ratios and to establish the ratio at which better results are obtained.